PENGARUH STRUKTUR CORPORATE GOVERNANCE PADA YIELD TO MATURITY OBLIGASI MELALUI PERINGKAT OBLIGASI - Putri, I Gusti Agung Pramesti Dwi; Rasmini, Ni Ketut; Mimba, Ni Putu Sri Harta (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
This study aims to examine the effect of Corporate Governance (CG) structure on bond Yield To Maturity (YTM) using bond rating as the intervening variable. The population of this research covered all corporate bonds that listed i n Indonesia Stock Exchange in 2013 to 2015. The sampling technique is purposive sampling method . Data analysis techniques used in this study is the path an a lysis. This research prove s that institutional ownership, board size, audit committee, and bond rating negatively affect s bond YTM. Managerial ownership positive ly affects bond YTM. Institutional ownership, board size , and audit committee positive ly affects bond rating. Managerial ownership negative ly affect s bond ratings. B ond rating shown mediate d the association of institutional ownership on bond YTM, the association of board size on bond YTM, and the association of the audit committee on bond YTM. However, bond rating can not mediate the effect of managerial ownership on bond YTM.   Keywords: corporate governance structure , bond yield to maturity , bond rating